2006
DOI: 10.1002/nau.20339
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiotensin II in stress urinary incontinence: A rat model

Abstract: Aims: Pharmacological treatment for stress urinary incontinence (SUI) is limited to the use of nonselective alpha-agonists, which are often ine¡ective. Non-adrenergic mechanisms have also been implicated in urethral closure, including angiotensin II (Ang-II), which has been demonstrated throughout the urinary tract. We investigate the role of Ang-II in urethral tone in a rat model of SUI. Methods: Abdominal leak point pressure (ALPP) and retrograde urethral pressure pro¢lome-try (RLPP) were measured in 70 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…1 NCNA mechanisms implicated in the urethral sphincter action have been described previously. Phull et al 2 observed that the blockade of angiotensin II receptors type 1 (AT1) and type 2 (AT2) decreases urethral resistance in stress urinary incontinence rat model. Moreover, angiotensin II treatment improves urethral tone in sphincter deficiency in the rat model.…”
mentioning
confidence: 99%
“…1 NCNA mechanisms implicated in the urethral sphincter action have been described previously. Phull et al 2 observed that the blockade of angiotensin II receptors type 1 (AT1) and type 2 (AT2) decreases urethral resistance in stress urinary incontinence rat model. Moreover, angiotensin II treatment improves urethral tone in sphincter deficiency in the rat model.…”
mentioning
confidence: 99%
“…The lower urinary tract harbors a local renin-angiotensin system [30] that contributes to stress incontinence in animal models [31]. A post hoc analysis of antihypertensive patients treated with AT 1 receptor blockers revealed lesser lower urinary tract symptoms than the untreated subjects [32].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most used methods to evaluate urethral resistance in rats is the determination of LPP (11). In these animal models, the intravesical pressure can be evaluated by urethral or suprapubic catheter (12,13). However, to determine the LPP in rats requires a very well trained investigator to eliminate confounding variables, especially because the LPP evaluation can trigger micturition and urethral catheter may increase the urethral resistance (14).…”
Section: Discussionmentioning
confidence: 99%